Interpretasi Audiens pada Pasangan Suami Istri dalam Program KB Vasektomi di Youtube Channel Kang Dedi Mulyadi : (Analisis Resepsi pada Masyarakat Klapanunggal, Bogor) - Muhammad Rifai; Nawiroh Vera (Yayasan Pendidikan Penelitian Pengabdian Algero, 2026)
The development of digital media, especially YouTube, has become an important tool in disseminating social issues, including the Family Planning (FP) program. One of the contents that has attracted public attention is a video on Kang Dedi Mulyadi's YouTube channel entitled